Ripoliticizzare la vulnerabilità. I Peul del Sahel di fronte al cambiamento climatico, alla crisi alimentare e all’instabilità politica - Ciavolella, Riccardo (L’Uomo società tradizione sviluppo, 2022)
This paper aims at formulating a critique of the relationship between food crisis and political instability in the Sahel, especially in relation to Fulani herders communities. Scholars have often focused on systems of production and Human-Nature relationships when analyzing these populations of nomadic origins. But nowadays, it is necessary to update the interpretation of these phenomena in the light of new dynamics. Today, international development and governance actors aims at using some neo-Malthusian perspectives, which interpret the Sahel food crisis as an immediate and direct effect of a crisis of production linked to the deterioration of climatic conditions. Thus, they restore in the scientific debate the idea of a direct relation of action/reaction between Nature and Human beings. For instance, they interpret as an adaptive strategy every type of mobility, from the variation of transhumance pathways to the international migration of a new category of subjects (“environmental refugees”), who are supposed to enter Europe to flee food crisis. On the contrary, a deeper interpretation of environmental and food crisis in the Sahel shows that it is not a direct relationship: some political reasons are at stake as elements of instability and vulnerability. In order to understand these dynamics, the paper stems from an “emic” interpretation of these communities' modes of reaction and the way in which they elaborate an idea of “risk” and “vulnerability”. In these imaginaries, the food and environmental crisis are often intertwined to the political instability, which need an analysis of how these populations define and put accountability and responsibility for their condition to human, natural or other forces.